Miss the presence and get used to the virtuality of the secondary school in Argentina. Feelings of young students in the pandemic context (Praxis Educativa, 2022)
COVID-19 pandemic led to a class suspension in school buildings and their activities passed to digital platforms, generating an abrupt change in the lives of those who belong to the educational community. Through a virtual survey, this article inquires the school experience of young students that attended secondary school from seven Argentinian provinces during the so called “process of pedagogical continuity”. The results show the students who have better conditions to get through this process, in terms of connectivity, technology and school conditions, are those who express difficulties in the adaptation of electronic learning, they miss sociability with their classmates and the on-site interaction with their teachers, and they also feel they didn’t organize their study time better than before the pandemic. Based on these findings, interpretative hypotheses are suggested about the impacts left by the pandemic.
Keywords: distance education; school time; secondary school students; adolescence; pandemics; Educational sociology